Análise dos instrumentos organizacionais e políticos para a construção da cadeia produtiva do pinhão no Rio Grande do Sul - Santos, Elke Lima dos (2018)
The present study analyzes the scenario about commercialization of pinion nut, as a non-timber product, as well as the political and organizational actions to build its productive chain, in comparison with Brazil Nut marketed in the north of the country. This study had as main objective to identify and discuss the existing mechanisms for the commercialization of pinion, aiming the promotion and development of his productive chain through application of an open questionnaire, divided into three topics according to the question themes, having as targets stakeholders linked to research and commercialization of both non-timber forest products. Based on the information collected, elaborated three topics of discussion entitled: 1. Characterization of chain and social organization, 2. Quantities, values and processing, 3. Public Policies and actions related to the pinion and Brazil Nut production chain. With the research, it concludes that historical question are related to the difference in the current situation of these products commercialization. Also the pinion presents itself as a product with secondary representativeness next to the income formation of producers involved in the production chain, as it happens with Brazil Nut in the north of Brazil, which contributes so that the commercialization structure of the pinion turn incipient and requires the organization of civil society, as well as greater interest and attention on the part of the public power with actions that involve entities that can assist in different areas, as well as grant technical assistance, research and financial support. Another relevant factor is that due to its excellent nutritional properties, several researches are underway to use the pinion for the most diverse purposes, the processing for turn into base product, such as the pinion nut flour being presented both, for the producer as to the literature, as the great strategy for the insertion of pinion in the consumer market with the capacity to compete with the other existing flours, due to their differentiated characteristics. Therefore, it is concluded that financial incentives and public policies are the main actions identified in the research for the structuring and consolidation of NTFP productive chains, therefore, the greatest responsibility for this is the responsibility of the public power, with its attention and actions so that civil society is encouraged to organize and, thus, to generate a real movement for the creation and permanence of the product chain of the socioeconomic biodiversity of the Brazilian extractivists, mainly pinion.